An EEG Study on the Effects of Induced Spiritual Experiences on Somatosensory Processing and Sensory Suppression - van Elk, Michiel (Journal for the Cognitive Science of Religion, 2015)
In the present EEG study a placebo God Helmet was used to induce spiritual experiences in the lab, by boosting the expectations and suggestibility of participants. At a behavioral level it was found that instructions regarding whether the helmet was turned on or off were not effective, but that individual differences in beliefs in the effectiveness of the helmet, magical ideation, absorption and paranormal beliefs were strongly related to induced spiritual experiences. At a neural level, believers compared to skeptics were characterized by trend for increased theta / alpha power during the helmet session and trend for a reduced auditory suppression of the P2 component. These novel findings indicate that individual personality differences are a strong predictor of induced spiritual experiences and that reduced sensory suppression may reflect a reduced pre-reflective sense of agency, which in turn could underlie proneness to self-induced spiritual experiences.